MULTICRITERION OPTIMIZATION AT EVOLUTIONARY SEARCH FOR TUBULER GAS HEATERS - Дудкін, Костянтин; Іродов, В’ячеслав (SWorldJournal, 2025)
The task of finding an optimal solution for a known binary fuzzy choice relation is considered. An iterative algorithm is used, in which the functions of generation and selection of solutions with several branches of the evolutionary search are successive